2014
DOI: 10.1371/journal.pone.0099609
|View full text |Cite
|
Sign up to set email alerts
|

Severe Eczema in Infancy Can Predict Asthma Development. A Prospective Study to the Age of 10 Years

Abstract: BackgroundChildren with atopic eczema in infancy often develop allergic rhinoconjunctivitis and asthma, but the term “atopic march” has been questioned as the relations between atopic disorders seem more complicated than one condition progressing into another.ObjectiveIn this prospective multicenter study we followed children with eczema from infancy to the age of 10 years focusing on sensitization to allergens, severity of eczema and development of allergic airway symptoms at 4.5 and 10 years of age.MethodsOn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 45 publications
0
15
1
1
Order By: Relevance
“…Similarly, the Consortium of Food Allergy Research Observational Study reported that children with history of atopic dermatitis had higher peanut sensitization when exposed to peanut and the sensitization rates was further increased in those with severe atopic dermatitis [ 25 , 26 ]. Other studies reported the association between eczema severity and asthma [ 29 , 30 ], which we did not observe in our cohort.…”
Section: Discussioncontrasting
confidence: 93%
“…Similarly, the Consortium of Food Allergy Research Observational Study reported that children with history of atopic dermatitis had higher peanut sensitization when exposed to peanut and the sensitization rates was further increased in those with severe atopic dermatitis [ 25 , 26 ]. Other studies reported the association between eczema severity and asthma [ 29 , 30 ], which we did not observe in our cohort.…”
Section: Discussioncontrasting
confidence: 93%
“…Finally, in a prospective Swedish study of a cohort of 115 children with AD aged under 2 years, AD severity was not only associated with a higher risk of asthma at 10 years ( P = .01), but also with a higher risk of allergic rhinitis ( P = .01) …”
Section: Methodsmentioning
confidence: 96%
“…Ekbäck et al 20 showed that infantile eczema with high scoring atopic dermatitis (SCORAD) points (scoring of AD severity) was associated with an increased risk of asthma at 10 years of age. Children with eczema and wheezing episodes during infancy are more likely to develop asthma than infants with eczema alone.…”
Section: Infantile Eczema and Its Association With Development Of Atomentioning
confidence: 99%